Our constitution. By Shad Salem Faruqi - Wan Muhammad, Ramizah (IIUM Press, 2020)
The book under review, written by an acknowledged constitutional law expert, Shad Saleem Faruqi, provides a good and clear understanding of the Malaysian Federal Constitution.